Assessing the efficiency Economic performance of the diyala General company for electrical industries for the Period (2000-2010) - رشيد ثائر محمود; عبد الله علي وهيب (Journal of Economics and Administrative Sciences, 2014)
Facing industrial companies many pressures and challenges due to rapid changes in the business environment of contemporary, which requires them to do their performance look more inclusive rather than limiting performance evaluation on the financial perspective in spite of its importance, prompting companies to rethink their reality competitive through the adoption of methodologies and new philosophies to manage competitiveness of total quality management, and re-engineering of production processes, and knowledge management,... etc., as This study framework cognitive and practical "to evaluate the performance of a company Diyala General Electric Industries and how to rehabilitate in light of the options and alternatives strategy available, due to problems experienced by companies Diyala General under exposure trade of goods and services and weak competitiveness, and aims to stand on the results of evaluating the performance of the company for the development of alternatives and options Alstratejahlaadh rehabilitation company to correct its course to raise the competitiveness of the industry itself, in light of the speed changes in the economic environment domestically and internationally, in order to prophylaxis of their standard competitive to keep up with technological developments and industrial. study included three axes president, the first dealing with (the concept of assessment Aladaoualaguetsada and analysis strategic environment industry) The second phase offender Applied to study, which showed efficient economic performance of companies Diyala during the search, which led to lack of capacity utilization productivity of the company as required as well as the intensity of competition for industrial products, it all led to not to create added value to the desired level, which in turn led to low volume profit in the company as a whole, and the third dealt with ways to improve the competitive company Diyala within the vision and rehabilitation of the company. The study concluded with a number of conclusions and propose some solutions that suit and the possibility of the state and the requirements of the future stage to contribute to raising the competitiveness of the company.